2022
DOI: 10.1002/bit.28104
|View full text |Cite
|
Sign up to set email alerts
|

Combined multivariate statistical and flux balance analyses uncover media bottlenecks to the growth and productivity of Chinese hamster ovary cell cultures

Abstract: Chinese hamster ovary (CHO) cells are widely used for producing recombinant proteins. To enhance their productivity and product quality, media reformulation has been a key strategy, albeit with several technical challenges, due to the myriad of complex molecular mechanisms underlying media effects on culture performance. Thus, it is imperative to characterize metabolic bottlenecks under various media conditions systematically. To do so, we combined partial least square regression (PLS‐R) with the flux balance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Our study found that ammonia is the most important feature among the others based on its contribution to the model accuracy in predicting one‐step ahead of VCD (Supplementary Figure S1). In fact, ammonia is a waste byproduct of cell metabolism and its accumulation in the culture medium can have a negative impact on cell growth and viability, as an inhibitory and toxic metabolite (Yeo et al, 2022). Additionally, the production and accumulation of ammonia vary depending on the specific cell line and culture conditions (Genzel et al, 2005; Kim et al, 2013; Ozturk et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that ammonia is the most important feature among the others based on its contribution to the model accuracy in predicting one‐step ahead of VCD (Supplementary Figure S1). In fact, ammonia is a waste byproduct of cell metabolism and its accumulation in the culture medium can have a negative impact on cell growth and viability, as an inhibitory and toxic metabolite (Yeo et al, 2022). Additionally, the production and accumulation of ammonia vary depending on the specific cell line and culture conditions (Genzel et al, 2005; Kim et al, 2013; Ozturk et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, we previously developed a data-driven and in silico model-guided systematic framework to investigate the effect of growth (basal) media on CHO cell culture performance, as such successfully suggesting the new media formulations for the enhanced growth and final titer. [32,33] Similarly, well-designed and tailored targets of nutrients for feed media can be explored using the framework. It should be noted that the composition of the feed media is typically more complex than basal media since many include additional amino acids, vitamins, trace elements, and other supplements that are not present in the basal media.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, we previously developed a data‐driven and in silico model‐guided systematic framework to investigate the effect of growth (basal) media on CHO cell culture performance, as such successfully suggesting the new media formulations for the enhanced growth and final titer. [ 32,33 ]…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, in our previous study, we developed data-driven and in-silico model-guided systematic framework to investigate the effect of growth media on CHO cell culture performance, allowing us to design the new media formulations for enhanced productivity. [33,34] In fact, most of the biologics based on CHO cells are manufactured using fed-batch process. Since basal media may not contain all of the specific nutrients and growth factors required to support high levels of cell growth and productivity, feed media are typically supplemented to the basal media regularly during the culture process to provide additional nutrients and growth factors that are required for improving cell growth, productivity, and viability.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, in our previous study, we developed data-driven and in-silico model-guided systematic framework to investigate the effect of growth media on CHO cell culture performance, allowing us to design the new media formulations for enhanced productivity. [33,34]…”
Section: Introductionmentioning
confidence: 99%